2009
DOI: 10.17221/63/2009-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Differences in top-soil features between beech-mixture and Norway spruce forests of the Šumava Mts.

Abstract: Top-soil samples were taken from four mountain forest ecosystems in the Bohemian Forest to compare the processes in European beech-mixture (fs) and Norway spruce (Pa) dominating ecosystems. Selected plots can be grouped into two types of forest ecosystems which are conditioned by position on the natural altitudinal gradient. Several chemical features (content of organic matter, properties of humic and fulvic acids, releasable P, Ca, Mg, Fe and Al content) were compared with the species structure of oribatid mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…The opposite trend was recorded in forests undergoing bark beetle gradation. There were lower total abundance (approximately 80-100 000 ind./m 2 ) and number of species compared to our results from the regenerating forest, and oribatid community was even more dominated by T. velatus (Mateˇjka and Stary´2009).…”
Section: Species Compositioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The opposite trend was recorded in forests undergoing bark beetle gradation. There were lower total abundance (approximately 80-100 000 ind./m 2 ) and number of species compared to our results from the regenerating forest, and oribatid community was even more dominated by T. velatus (Mateˇjka and Stary´2009).…”
Section: Species Compositioncontrasting
confidence: 97%
“…The results obtained in the regenerating forest were compared with data from unaffected, mature spruce forest and from bark-beetle gradation. Data for comparison were taken from literature (Siira-Pietika¨inen et al 2001;Stary´2003;Materna 2004;Mateˇjka and Stary´2009;Č uchta et al 2012;L ó sˇkova´et al 2013;Farska´et al 2014). We used principal component analysis (PCA) to show main gradients in the communities.…”
Section: Statisticsmentioning
confidence: 99%
“…The HA and HA/FA ratio rises with the increasing proportion of spruce. A higher content of humic acids under spruce stands than under beech stands was reported by Matějka et Starý (2009). The evaluation of humus quality according to the HA/FA ratio is problematic in humification horizons and need not fulfil the hypothesis presented by Note: S 1 -instantaneous content of exchange base cations (mmol/kg); T (CEC) -cation exchange capacity (mmol/kg);V -base saturation (%) some authors (Zacanda et al 2003, Slepetiene et Slepetys 2005) that humus quality rises with the increasing content of humic acids.…”
Section: Humification Horizons and Their Influencing By The Species Cmentioning
confidence: 75%
“…This hypothesis was confirmed by the study of Kacálek et al (2010), who evaluated the soilimprovement influence of tree species on the formation of forest floor in the afforestation of agricultural lands at the foothills of the Orlické hory Mts. Matějka et Starý (2009) laid out an experiment in the Šumava Mts., where the condition of top soil layers was compared under spruce and beech stands. In their study these authors reported a higher content of magnesium under beech stands.…”
Section: Humification Horizons and Their Influencing By The Species Cmentioning
confidence: 99%
See 1 more Smart Citation